The spirit of Islam in Javanese mantra: Syncretism and education - Pamungkas, Onok Y. (HTS teologiese studies, 2023)
The history of the development of Islam in Indonesia often fails because of the rejection of the local community. Therefore, it is necessary to make ethical efforts so that society can accept Islam. This research is an attempt to explain the Mantra by Sunan Kalijaga (after this referred to as SKM) as a medium for spreading Islam. This research uses a qualitative research paradigm. The primary data source is the spell text in Serat Kidungan ingkang Jangkep. Data analysis techniques use content analysis techniques and hermeneutics. The results showed that SKM is a philosophical representation of Javanese mantras with the spirit of Islam. Mantras are not simple texts but rather acts of establishing the understanding of Islam through integrating literature and culture. Hindu-Islamic syncretism is wrapped in the symbolisation of the text. Word choice is not always of magical significance because the text is oriented towards the purpose of ‘the other’. Restructuring the relationship between text and symbols reflects a strategy for changing the nature and purpose of spells. In turn, SKM is a quality ritual language that has an essential role in the history of the Islamic movement in Java, Indonesia. Axiologically, SKM provides necessary educational knowledge about the ethics of proselytising without being hurt. Sunan Kalijaga combines literary, cultural, educational, and ethical values for religious purposes. An important implication of this research is that mantras can contribute to promoting the transdisciplinary aspects of religion in the international theological arena through mantra texts. Thus, SKM has an essential role in spirituality and science.Contribution: This article contributes to the HTS Theological Studies’s goal of promoting the transdisciplinary aspects of religious studies in the international theological arena on the study of mantra texts.